Serviço de gerenciamento da Terapia Medicamentosa em um ambulatório de Diabetes: - Georgiane de Castro Oliveira (2016)
Medication therapy management (MTM) is a clinical service grounded in the methodological and theoretical framework of pharmaceutical care. To achieve best clinical, humanistic and economic results, MTM should be inserted into the team through a shared practice. There are some fundamental skills for teamwork and interprofessional relations models that may be followed. The aim of this research was to understand the interprofessional relations and challenges for the provision of MTM by the pharmacist inserted in the health team, through shared practice. This study was developed using the critical ethnography methodology. Data collection included individual semistructured interviews with fourteen team members, and participant observation, with field notes during 17 months. Based on the systematic data analysis, four main categories were founded: 1. Understanding inter-relationships, 2. Sharing the care, 3. Clarifying the challenges in the way of shared care and 4. Drawing a path to the patient-centered care. To achieve understanding of the inter-relationships was important to address the facilitators to build this relationship, including accessibility, communication, trust, harmony, respect and long experience. In addition, the definition of roles and the understanding of the professional limit were appointed as fundamental to the construction process. In the care sharing category, was scored the importance of patient referral partners among professionals, enhancing confidence in the team. Furthermore, it was pointed out the need to build shared therapeutic targets to be considered shared care. The challenges for the shared care included infrastructure limitations, staff turnover and lack of institutionalization. Another challenge found is the complexity of the patient's demand. To overcome these challenges, the team has listed some changes, such as reorganization of care, improved documentation and maintenance of a case discussion of routine. It was also noted the existence of power relations in health teams, especially the medical power and, consequently, medical resistance in the shared work. In the final category, an integrated training path has been proposed, with the deconstruction of the currently existing individualizing training in healthcare courses. This work allowed the understanding of the dynamics of inter-relationships and shared care, in a scenario where the GTM service is inserted in the health team. Understanding the work process in a team is important to the emergence of new collaborative initiatives and allows training focused on the care sharing.